2020
DOI: 10.1371/journal.pone.0226879
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis of maintenance therapy in chronic lymphocytic leukemia

Abstract: Background Chronic lymphocytic leukemia (CLL) is incurable through conventional chemoimmunotherapy regimens. Despite durable responses to front-line therapy and sustained remission rates in patients with CLL, a majority of patients eventually relapse in 5 years of initial treatment. The depth of the response may affect the length of response. Maintenance therapies were aimed to deep remissions and extend the period of disease quiescence. Lenalidomide, rituximab and ofatumumab had demonstrated some efficacy as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Overall, 138 records were retrieved: 13 fully published MAs reported PFS or OS ( Table 1 and Table 2 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and 10 MAs reported safety outcomes ( Table 3 ) [ 8 , 9 , 11 , 15 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 138 records were retrieved: 13 fully published MAs reported PFS or OS ( Table 1 and Table 2 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and 10 MAs reported safety outcomes ( Table 3 ) [ 8 , 9 , 11 , 15 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous network meta-analysis had shown that maintenance therapies achieved superior effect in prolonging progression-free survival (PFS) compared without intervention. Moreover, the therapy did not significantly increase the risk of overall serious adverse events (SAE) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different CLL populations may benefit from an individualized approach that considers risk factors and prognosis (e.g. age, stage, immunoglobulin heavy chain [ IGHV ] status, del11q and del17p abnormalities, TP53 gene mutations), and treatment preferences 6‐8 . Many patients have comorbidities, which may have an adverse impact on treatment, precluding them from standard chemoimmunotherapy (CIT) and affecting OS.…”
Section: Introductionmentioning
confidence: 99%